Fade away - Coben, Harlan 1962- (Great Britaian clays ltd, ives plc, 1988)
For sports agent Myron Bolitar, the disappearance of a man he'd once competed against was bringing back memories--of the sport he and Greg Downing had both played and the woman they both loved. Now, among the stars, the wanna-bes, the gamblers and groupies, Myron is unraveling the strange, violent life of a sports hero gone wrong, and coming face-to-face with a past he can't relive, and a present he may not survive
"A Myron Bolitar novel" --jacket cover
"Dell mass market edition published December 1996"--T.p. verso
1
Keywords: Bolitar, Myron -- (Fictitious character) -- Fiction; Basketball players -- Crimes against -- Fiction; Sports agents -- Fiction; New Jersey -- Fiction; Mystery fiction